Evaluation of the implementation process of the classroom platform at UNAH 2020 - Zambrano Arce, César Teófilo (2021)
This study is based on the evaluation process of the university public policy of distance education and, specifically, the implementation of the Classroom platform, in its didactic and operational dimensions, at the National Autonomous University of Huanta (UNAH), period 2020, in the context of physical and social isolation, which allowed an accurate analysis to make decisions in this regard. To measure such impact, the non-experimental scientific method, descriptive level, was used; likewise, the survey technique, whose instrument is the questionnaire, which was applied to the population of the ordinary teaching staff of the institution. The conceptual frameworks are enriched, exposing reflections from a detailed bibliographic review that analyzes indicators of content, activities, interactivity, resources, administration and aesthetics of the virtual environment. From the analysis of the dimensions, it appears that an average 90% of teachers have carried out the platform implementation process successfully.